Couchsurfing in China: Guanxi networks and trust building. (March 2023) - Huang, Xiang; Cui, Qingming; Chen, Zhao
Trust building is a core issue in couchsurfing; however, existing research has mainly focused on trust formation in Western culture and ignored other cultural contexts. This article examines couchsurfing practices in China and explores the influence of Chinese guanxi on trust formation. The results show that the general process of trust building between Chinese couchsurfers is similar to that of Western surfers, but there are also some important cultural differences, including the mandatory identity authentication required by the Chinese couchsurfing website, which builds trust in the social system. In China, gift-giving practices and social gatherings are also important in building guanxi to gain lasting trust. Finally, the guanxi between friends and acquaintances can greatly facilitate surfers' ability to find accommodation resources and build trust. Guanxi generates a novel trust formation model based on personal networks in shared hospitality in contrast to the much-researched system trust and interpersonal trust.